ИННОВАЦИОН ЁНДАШУВ НЕГИЗИДА МУҲАНДИСЛИК ОБЪЕКТЛАРИНИ ЛОЙИҲАЛАШ ВА КОНСТРУКЦИЯЛАШ (ВАЛЛАРНИ МУСТАҲКАМЛИК ВА БИКРЛИККА ҚИЁСИЙ ҲИСОБЛАШ МИСОЛИДА) - Набиев, А.Н.; Саидова, Д.Ш. (SCIENCE and SOCIETY, 2024)
The article substantiates the integrity of the design and construction processes based on innovative CAD/CAE/CAM technologies and the high efficiency of using MathCad software in the calculation and design of shafts for strength and stiffness.